2017
DOI: 10.1136/neurintsurg-2017-013534
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy performs similarly in real world practice: a 2016 nationwide study from the Czech Republic

Abstract: Data on efficacy, safety, and logistics of MT from the CR were similar to data from the HERMES collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…Preliminary reports from monocentric (12, 13) or multicentric (14, 15) studies indicate that EVT seems applicable in the “real” world of clinical practice, with similar results to those of controlled trials. Still, little data is available on how systems of care have started to adapt to this paradigm shift in acute stroke therapy.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Preliminary reports from monocentric (12, 13) or multicentric (14, 15) studies indicate that EVT seems applicable in the “real” world of clinical practice, with similar results to those of controlled trials. Still, little data is available on how systems of care have started to adapt to this paradigm shift in acute stroke therapy.…”
Section: Introductionmentioning
confidence: 72%
“…Previous limited monocentric ( N < 80 cases) (12, 13) as well as larger multicentric studies (14, 15) of thrombectomy showed that comparable outcomes could be achieved in clinical practice and randomized trials. In 2015–2016, >85% of patients with M1 occlusion admitted in our center were treated by thrombectomy.…”
Section: Discussionmentioning
confidence: 95%
“…Results from individual hospital case series of EVT performed by interventional radiologists have demonstrated outcomes comparable to those of international trials (39)(40)(41)(42)(43)(44). At present, there are no publications including the Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials (HERMES) data that show different outcomes associated with interventional radiologists compared with neurointerventionists (4,45).…”
mentioning
confidence: 85%
“…Interventional radiologists have been partners with neurointerventional radiologists, endovascular neurosurgeons, and interventional neurologists in acute intervention for stroke (AIS) since the inception of EVT. Vascular/IR physicians who were not trained in formal neurointerventional fellowships have historically provided and continue to provide EVT in substantial numbers with good outcomes, comparable to those achieved by neurointerventional physicians during similar years (29)(30)(31)(32)(33)(34)(35). A recent survey of the Joint Commission (JC) PSCs found that 60% of the responding PSCs performed EVT, and, of these, 41% relied on IR physicians to provide this care (26).…”
Section: Evt Training Backgroundmentioning
confidence: 99%
“…The establishment of training guidelines to ensure competency standards that meet the needs of patients, hospitals, and physicians in these communities is relevant. It is intended that, by implementing and adhering to these training guidelines, the motivated diplomate in IR will be able to achieve competency to perform EVT with outcomes that meet published quality benchmarks (25) and are comparable to those of published registries and trials (4)(5)(6)(7)(8)(9)(10)16,17,19,35,(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Evt Training Backgroundmentioning
confidence: 99%